1989
DOI: 10.1007/bf03190854
|View full text |Cite
|
Sign up to set email alerts
|

Chronopharmacokinetic and bioequivalence studies of two formulations of trimipramine after oral administration in man

Abstract: The bioavailability of two oral formulations of trimipramine, tablets and solution, was performed in twelve healthy volunteers, in a cross-over study. Each formulation was administered in the morning after a fasted period, and in the evening after a meal, in order to evaluate the role of both administration time and food consumption on the plasma kinetic parameters, under usual therapeutic conditions. A high interindividual variability of data was found. First, the extent of bioavailability was identical for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…[30][31][32][33][34] Our finding of no difference in disposition of the highly cleared pro-drug MPS is consistent with these studies.…”
Section: Discussionsupporting
confidence: 90%
“…[30][31][32][33][34] Our finding of no difference in disposition of the highly cleared pro-drug MPS is consistent with these studies.…”
Section: Discussionsupporting
confidence: 90%
“…Various drugs show dosing time-dependent pharmacokinetics [23333435]. Imipramine is metabolized to desipramine by CYP1A2, 3A4, and 2C19, and imipramine and desipramine are hydroxylated to the 2-OH form by CYP2D6 [3637].…”
Section: Discussionmentioning
confidence: 99%
“…20) However, there are few reports on the mechanism of the chronopharmacological activity of antidepressants, and the effects of other neural systems such as the noradrenergic system remain to be clarified. Since clinical studies have suggested that different drugs show different chronopharmacological profiles, [21][22][23][24] it is important to analyze various drugs with different mechanisms of action. In this study, we attempted to determine the effects of dosing time on the activity of the dual-action SNRI milnacipran with the use of the modified FST, and we analyzed the mechanism underlying milnacipran's chronopharmacological action.…”
mentioning
confidence: 99%